Performance reviews : evaluate performance, offer constructive feedback, discuss tough topics. - Harvard business review (20 minute manager series, 2015)
You've just world that it's time conduct annual performance reviews for your direct reports. You know these evaluations offer a great opportunities for change and grow-for stellar employees, subpar performers, and those between. But year after year, you find yourself ill prepared, and your assessment ands up being more of a formality than an opportunities for employee improvement. This book walks you through the step-by-step process of conducting performance reviews so you'll be better equipped when it comes time for this crucial task. You will learn to: - Use direct observation and other resources to make an objective assessment. - Formally document your evaluation.-Discuss both achievements and performance gaps. - Turn negative feedback into a productive conversation. Set changllenging but achievable goals. - Make feedback and follow-up an ongoing part of your job